Open Latarjet for Acute Anterior Dislocation with Severe Anterior Glenoid Rim Fractures Provides Stable but Arthritic Shoulder at Long-term Follow-up - Esteban Andres Lobos Centeno; Dominique Saragaglia; Vincent Martinel; Johannes Barth (The Hive)
Background: Large anterior glenoid rim fractures, known as Ideberg IIa, particularly those with persistent static subluxation despite appropriate immobilization, are best treated by reduction and internal fixation, utilizing either open or combined arthroscopic techniques. Purpose: This study evaluated functional and radiological results of acute shoulder dislocations, associated with a large bone avulsion of the antero-inferior glenoid rim, treated with a modified Latarjet procedure. Materials and Methods: From January 1991 to December 2000, 12 patients were admitted with an acute anterior dislocation associated with an anterior glenoid rim fracture greater than one-third of its glenoid surface. The sample was composed of 7 males and 5 females. Ten of them underwent an Open Reduction and Internal Fixation, using the modified Latarjet procedure. A standard deltopectoral approach was used, followed by coracotomy and reduction of the glenoid fragment, fixed with a 3.5 mm cortical screw. The coracoid graft was then placed in front of the fragment and secured with a malleolar screw, creating a “bone block sandwich”. The subscapularis tendon was reattached to its humeral stump. The Mean age was of 57 years old (range, 25-82). A direct trauma was involved in 67 % of the cases. The patients were assessed according to Constant score and had X-rays evaluation (Samilson criteria). Results: 9 of the 10 operated patients could be followed up. The Mean follow-up was 6 years (range, 3-11 years). None had shoulder instability. The mean Constant score was 82.2/100 (with a difference of 16.1 points compared to the other side). The mean weighted Constant score was 88.6/100. Two patients showed severe osteoarthritis images on the X-ray findings (stage 4). We also observed three stages 2, one stage 1, and two normal X-rays. In three cases, the coracoid bone block was slightly lateralized. Conclusion: The modified Latarjet procedure provided stable shoulder outcomes in patients with large glenoid rim fractures (>20%). However, glenohumeral osteoarthritis was observed in 63% of cases at mid- to long-term follow-up, regardless of age.